2022
DOI: 10.4254/wjh.v14.i11.1940
|View full text |Cite
|
Sign up to set email alerts
|

Current status of disparity in liver disease

Abstract: Disparities have emerged as an important issue in many aspects of healthcare in developed countries and may be based on race, ethnicity, sex, geographical location, and socioeconomic status. For liver disease specifically, these potential disparities can affect access to care and outcome in viral hepatitis, chronic liver disease, and hepatocellular carcinoma. Shortages in hepatologists and medical providers versed in liver disease may amplify these disparities by compromising early detection of liver disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Despite its cross‐sectional design, this study and the previous body of literature in this field have important implications for potential interventions at the individual, provider, and policymaker levels. Health disparities in liver disease are prominent among underserved racial/ethnic and lower socioeconomic groups, particularly in subgroups with the lowest incomes and limited resources 14,15 . The strengths of this study include the utilisation of a large number of participants who represented the US general population and an opportunity to analyse the recently updated dataset during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its cross‐sectional design, this study and the previous body of literature in this field have important implications for potential interventions at the individual, provider, and policymaker levels. Health disparities in liver disease are prominent among underserved racial/ethnic and lower socioeconomic groups, particularly in subgroups with the lowest incomes and limited resources 14,15 . The strengths of this study include the utilisation of a large number of participants who represented the US general population and an opportunity to analyse the recently updated dataset during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported age-stratified ticularly in subgroups with the lowest incomes and limited resources. 14,15 The strengths of this study include the utilisation of a large number of participants who represented the US general population and an opportunity to analyse the recently updated dataset during the COVID-19 pandemic. On the contrary, this study also presented the following limitations.…”
Section: Comparisons Of Outcomes Based On the Insurance Types Comorbi...mentioning
confidence: 99%
“…Hepatocellular carcinoma has a clear male predominance, but sex-specific differences remain not completely understood [29,30]. Females have a lower risk of developing HCC versus males with an approximate incidence rate ratio of 1:4 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplant (LT) is a life-saving treatment for end-stage liver disease, but access to this limited resource is highly competitive. 1 After the implementation of the Milan criteria in 1996, LT was used as the best treatment option in selected patients with hepatocellular carcinoma (HCC) and cirrhosis. 2 For allocation of LT, the model of end-stage liver disease (MELD) score is used, a numerical value based on creatinine, international normalization ratio (INR), and bilirubin, ranging from 6 to 40.…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplant (LT) is a life-saving treatment for end-stage liver disease, but access to this limited resource is highly competitive . After the implementation of the Milan criteria in 1996, LT was used as the best treatment option in selected patients with hepatocellular carcinoma (HCC) and cirrhosis .…”
Section: Introductionmentioning
confidence: 99%